Significant structural transformations of the Phonetic similarities in Surat AlBaquara (Journal of the College of Basic Education, 2022)
In the name of God the most gracious, the most mercifulAnd prayer and peace be upon the most virtuous creation of the Lord of the worlds,His honest Messenger Mohammed, and all his familyThe talk about miraclesin the systematic wording of theQuran isOld, as scholars left usa great legacy todraw from,over the centuriesandfor all the years to come. But thatbook’s facts are consistent, and its meanings are harmonic and its verbal structures and constructions are elevated by the Knowing Master, therefore all selves will always fall for it, reflect and study it till the end of time. God’s will bestowed on me the gift of ability to study a subject that has a connection to the esteemed book and perceive its miraculous verbal structures to comprehend the language of the precious quoran and its phonetic similarities exclusively, through analyzing the lingual structure which is based on the context to discover its purposes and truth.So this title (Significant structural transformations of the Phonetic similarities in Surat AlBaquara) is to clarify that the research lines pour in :1-.Connotation and meaning contained in what is distinguished of being similarities in the Holy Quran2- The field Applied for this study will only be in Surat AlBaquara , because the study of all similarities cannot be contained in a small research.3- Full understanding of the repeating of similar verses can only be by linguistic functions analysis : syntax, morphology, significance and vocals. So that we can notice the subtle differences between one verse and another that is similar to it. In all that I lean on the Koranic context and its significance, and perhaps that was the hardest of what I had to face, because it requires an updated understanding of the Quranic text.